2023
DOI: 10.1177/00343552221146159
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas: Current and Projected Concerns Reported by Certified Rehabilitation Counselors

Abstract: The purpose of this study was to investigate ethical dilemmas faced by certified rehabilitation counselors. Using a mixed-method survey approach, both quantitative and qualitative data were collected and analyzed. Thematic analysis was used to identify common themes among responses including the ethically challenging incident, additional resources to clarify the situation or reach resolution, projecting future ethical issues, approach to resolution for current ethical issues, and additional issues to address o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Hill and colleagues (2023) investigated the ethical dilemmas faced by CRCs in a 2019 mixed-methods study, in which several current telerehabilitation themes emerged, including confidentiality in digital platforms, boundaries in distance counseling, and limitations of agencies working as mobile providers.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill and colleagues (2023) investigated the ethical dilemmas faced by CRCs in a 2019 mixed-methods study, in which several current telerehabilitation themes emerged, including confidentiality in digital platforms, boundaries in distance counseling, and limitations of agencies working as mobile providers.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Discrepancies in content analysis between the 2010 and 2017 versions of the Code do not necessarily imply growth in this factor but could be explained by other measurement factors, such as different coding approaches by researchers. Hill et al’s (2023) survey performed for the 2023 revision found that Section K accounted for only 1.5% of the frequency of concerns by CRCs/CCRCs, second to last before Section I: Research and Publication . Both Sections I: Research and Publication and Section K: Business Practices were tied for last (each at .8%) in rank order of the Code sections as important when handling ethical issues.…”
Section: Brief History Of Rehabilitation Counseling In Forensic Settingsmentioning
confidence: 99%
“…It is essential for CRC’s to understand legislation and regulations as they pertain to the use of electronic health systems to maintain and store information regarding clients and client progress. In a review of ethical violations, though not prominent, violations regarding the use of technology were noted to be of continued occurrence (Hartley & Cartwright, 2015, 2016; Hill et al, in press; Tarvydas & Barros-Bailey, 2010). As CRCs, it becomes crucial to obtain consumer permission before engaging in services that rely on virtual counseling methods.…”
Section: Virtual Counseling In Vrmentioning
confidence: 99%
“…Even though ethical dilemmas did not present themselves in the section specific to Technology, additional concerns lie in areas of relationships and confidentiality. Recently, CRCs were surveyed regarding ethical dilemmas according to the 2017 Code; it is noteworthy to mention that the Technology section (Section J) was reported as an ethical dilemma by 18 of the respondents (Hill et al, in press). Compared with previous Code revisions, this is a substantial increase.…”
Section: Virtual Counseling In Vrmentioning
confidence: 99%
“…Section A of the Code provides structure to the counseling relationship, creates a safe space for the client, and protects vulnerable clients from harm (Remley & Herlihy, 2020). Many experts have discussed the importance of counseling relationships in the rehabilitation counseling process (Herlihy & Corey, 2015; Hill et al, 2022; Kocet & Herlihy, 2014; Lustig et al, 2002; Pope & Keith-Spiegel, 2008; Roberts et al, 2002). Issues around dual relationships or multiple counseling relationships are often complex and ambiguous (Remley & Herlihy, 2020).…”
Section: Purpose Of Section Amentioning
confidence: 99%